FINANCING MECHANISMS IN THE GREEN ECONOMY IN UZBEKISTAN - Allayarov Sukhrob Rustamovich (Sciental Journals Publishing, 2025)
Uzbekistan, located in Central Asia, faces environmental challenges such as water scarcity, air pollution, and the adverse impacts of climate change. In response, the country has adopted a green economy strategy, which integrates sustainable development principles across its key sectors. Central to this transition is the effective financing of green projects, including renewable energy, sustainable agriculture, and eco-friendly infrastructure. This article reviews the financing mechanisms available in Uzbekistan, including government policies, international partnerships, and private sector investments.
Keywords: Green economy, financing mechanisms, Uzbekistan, sustainable development, renewable energy, green bonds, international development assistance, public-private partnerships, climate finance.